Clinical Course and Prognosis of Long‐Term Survivors of Hepatocellular Carcinoma - Kim, Soon Sun; Lee, Jonghyun; Ahn, Sang Bong; Chon, Young Eun; Yoon, Eileen; Jeong, Soung Won; Jun, Dae Won (Alimentary pharmacology & therapeutics, 2025)
ABSTRACT Background and Aims This study investigated the long‐term prognosis and clinical course of patients who survived for more than 5 years after hepatocellular carcinoma (HCC) diagnosis. Methods This retrospective cohort study used data from the Korean National Health Insurance Service database. A total of 35,348 subjects newly diagnosed with HCC between January 2008 and December 2010 were followed up until December 2018. Results A total of 11,514 (32.6%) survived for 5 years after diagnosis of HCC among 35,348 patients diagnosed with HCC. Long‐term survivors (≥ 5 years) had a higher proportion of females, younger age, more frequent aetiology of hepatitis B virus, less frequent liver cirrhosis, diabetes mellitus and hypertension, and received curative treatment more frequently than nonsurvivors (< 5 years). The additional 1‐, 3‐ and 5‐year cumulative survival probabilities were 90.7%, 77.6% and 68.4% respectively. Patients who underwent curative treatment as the first treatment for HCC showed a higher additional 5‐year cumulative survival probabilities than those treated with noncurative therapy (74.5% vs. 64.2%). Among the long‐term survivors, 44.4% underwent HCC retreatment 5 years after HCC diagnosis. The additional 5‐year cumulative survival probability was 54.9% in the HCC retreatment group. The overall 5‐ and 10‐year cumulative probabilities of second primary malignancies in long‐term survivors were 15.36% and 27.54% respectively. The most frequent second primary malignancy was prostate cancer, followed by colorectal and pancreatic cancers. Conclusion Our study highlights that a significant proportion of patients with HCC achieve long‐term survival beyond 5 years, with favourable outcomes associated with curative treatments. A retrospective cohort study of 35,348 patients with HCC highlights that 32.6% achieved survival beyond 5 years. Curative treatments significantly improved outcomes, while secondary malignancies and retreatments shaped the clinical course of long‐term survivors.